Kesiapan Guru Sekolah Dasar dalam Implementasi Asesmen Diagnostik untuk Mendukung Pembelajaran Berdiferensiasi - Mailatul Jannah; Ika Maryani; Achadi Budi Santosa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to examine the readiness of elementary school teachers in implementing diagnostic assessment as part of differentiated learning. This study will describe teachers' understanding of the concept of diagnostic assessment, teacher skills in implementing it, obstacles, and efforts to overcome obstacles in implementing the assessment. The research method used is descriptive qualitative research involving interviews. The study shows that teachers understand the concept, purpose, and time of diagnostic assessment well. Teachers realize how important diagnostic assessment is to identify students' learning needs and design appropriate learning approaches. However, teachers still face several challenges when starting to implement diagnostic assessment, such as difficulty in compiling assessment materials, determining sentences that are easy to understand, and problems with assessment mapping and time constraints. To overcome this problem, teachers make various efforts, such as seeking further information. Further research should focus on developing and evaluating training programs specifically designed to improve teachers’ ability to develop and implement diagnostic assessments, examining the use of technology to assist teachers in developing, mapping, and administering diagnostic assessments, or conducting comparative studies with schools in other regions or schools with different contexts to gain a broader understanding of variation in diagnostic assessment implementation and factors that influence teacher readiness.